Psychosocial impacts of the COVID-19 pandemic on individuals with autism spectrum disorder: a systematic review (Research, Society and Development, 2022)
The COVID-19 pandemic forced national authorities to take unexpected measures, such as social isolation and social distancing. Within this context, individuals with Autism Spectrum Disorder (ASD) were greatly harmed, as they added the aforementioned symptoms to their pre-existing condition, raising the question of what were the psychosocial impacts of the COVID-19 pandemic in individuals with ASD. Systematic review made in the databases: Virtual Health Library and the National Library of Medicine from United States of America . Inclusion criterias were: written in Portuguese, English or Spanish, between December 2019 and December 2021, being within ethical research standards and being field research studies. The exclusion criterias were: articles unrelated to autism or COVID-19, reviews, editorials and opinion articles. It was identified that individuals with ASD were only benefited from social distancing if it did not lead to major changes in their routine. The family aspect showed to be divergent between approximation versus conflict between peers. The question of virtual social network has become an anxiety-generating factor for these individuals. With regard to mental health, this was definitely the most affected, with significant increases in levels of anxiety, stress and depression, generated by the changes in routine and the difficulty of continuing with their treatments. It was evident, therefore, that individuals diagnosed with ASD suffered numerous losses during the pandemic, especially in their mental health. It became clear that it is essential to understand them, given the difficulties with socialization and its consequences on mental health, their skills in the midst of work and their relationship with digital socializing.